Low phase‐noise high output power 176‐GHz voltage‐controlled oscillator in a 130‐nm BiCMOS technology. Issue 14 (30th August 2019) - Bello, Habeeb; Pantoli, Leonardo; Ng, Herman Jalli; Kissinger, Dietmar; Leuzzi, Giorgio
Abstract : In this study, the authors present the design and measurement results of a voltage‐controlled oscillator (VCO) that is based on a Colpitts core topology and a cascade output buffer. The circuit has a centre frequency of 176 GHz and is implemented in a 130 nm SiGe BiCMOS technology provided by IHP foundry. The VCO is a differential fundamental wave tunable oscillator that makes use of a transistor‐based LC‐resonator. On‐wafer measurements show a tuning range of about 5% from 171 to 179.5 GHz. The circuit achieves a maximum output power of 7.3 dBm when biased at 1.6 V and 6.5 dBm if biased at 1.4 V, both with an efficiency of ∼ 6.6%. DC power consumption is 82 and 52 mW, respectively. The measured phase‐noise of the VCO is − 110 dBc/Hz at 10 MHz offset. The VCO demonstrates state‐of‐the‐art performance at these frequencies with very good performance in term of output power, efficiency linearity, phase noise and compactness; in addition, thanks to the proposed architecture it shows high integrability at the system level.